A preparation method of anode for electrolytic water sterilization and disinfection device, and a durability performance testing device and method

Through hot press sintering and the use of palladium and platinum mixtures with strong oxidation resistance, the problems of uneven anode and insufficient durability are solved, and the service life and durability of the anode are significantly improved.

CN116102127BActive Publication Date: 2025-03-07XIAN TAIJIN NEW ENERGY & MATERIALS SCI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310162214.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-03-07
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The anode in the existing electrolytic water sterilization disinfection device is prone to unevenness during the preparation process of high-temperature sintering, which leads to short circuit problems and insufficient durability.

Method used

The hot press sintering method is used to improve the bonding force between the anode coating and the titanium substrate, reduce unevenness, and use a mixture of palladium and platinum with strong oxidation resistance as the base coating solution to enhance the oxidation resistance of the anode.

Benefits of technology

It significantly improves the service life of the anode, reduces the probability of short circuit, and improves the flatness and durability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116102127B_ABST
    Figure CN116102127B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrode material preparation and disinfection and sterilization technology, and discloses a method for preparing an anode for an electrolytic water sterilizer, a durability test device and a method, wherein the preparation of the anode includes the following steps: cutting and forming, sandblasting, heat leveling, acid treatment, cleaning, drying, configuring a bottom coating liquid, configuring an active layer coating liquid, coating, and hot pressing and sintering; the durability test device includes a liquid storage tank, a peristaltic pump, a power supply, a relay, and an electrolytic cell, wherein the relay is connected to the electrolytic cell through a wire; the electrolytic cell is provided with an overflow port, and the overflow port is connected to the liquid storage tank; one end of the peristaltic pump is connected to the liquid storage tank through a pipeline, and the other end is connected to the electrolytic cell through a pipeline. The present invention uses a hot pressing and sintering method, which can greatly improve the bonding force between the anode coating and the titanium substrate, and can also solve the unevenness of the anode caused by the high-temperature sintering preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode material preparation and disinfection and sterilization, and specifically relates to a method for preparing an anode for an electrolytic water sterilization and disinfection device, and a durability performance testing device and method. Background Art

[0002] Smart household sterilizers can use ultraviolet light, ozone, electrolyzed water, etc. However, both ultraviolet and ozone sterilization have disadvantages to varying degrees, such as the short service life of ultraviolet lamps, large investment and high cost of ozone disinfection equipment, poor sterilization continuity, and the need for assistance. Electrolyzed water sterilization is widely used because of its convenient material acquisition, low cost, and good sterilization effect. The sudden rise of the smart electrolyzed water sterilization market for civilian household appliances has also brought a series of problems, among which how to obtain a product with excellent durability and can withstand the impact loss of the reverse current generated by the equipment switch on the anode for a long time, and how to judge the durability of the anode sheet have become problems that the market urgently needs to solve.

[0003] Patent CN103014755B discloses a method for preparing a long-life titanium-based electrode. A titanium oxide layer is first prepared on a titanium substrate by an impregnation-thermal decomposition method, and then the titanium oxide layer is reduced in a reducing atmosphere. Then, tin metal and antimony metal are deposited on the surface of the titanium oxide layer in proportion by an electrodeposition method. After thermal oxidation, the antimony-doped tin oxide layer and the titanium oxide layer directly connected to the titanium substrate are tightly combined to form a solid solution structure. The titanium-based tin dioxide electrode prepared by this invention has the advantages of long service life, high oxygen evolution potential, high electrocatalytic activity, high efficiency of ozone production by electrolysis of water, etc., and the preparation process cost is low, the equipment requirements are low, the operation is easy to control, and it is convenient for industrial large-scale production. However, this invention will cause the surface of the electrode made of titanium substrate to be uneven, and short circuit problems may occur during use.

[0004] In view of the deficiencies in the prior art, the present invention proposes a method for preparing an anode for an electrolytic water sterilizer, and a durability performance testing device and method. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an anode for an electrolytic water sterilizer, a durability testing device and a method. The present invention uses a hot pressing sintering method, which can greatly improve the bonding strength between the anode coating and the titanium substrate; the present invention uses a hot pressing sintering method, which can solve the unevenness of the anode caused by the high-temperature sintering preparation process, and reduce the probability of the anode causing a short circuit during the electrolysis process due to unevenness.

[0006] The technical solution adopted by the present invention is a method for preparing an anode for an electrolytic water sterilizer, comprising the following steps:

[0007] Step 1, cutting and forming: cutting and forming the titanium substrate;

[0008] Step 2, sandblasting: performing surface sandblasting on the titanium substrate treated in step 1;

[0009] Step 3, thermal leveling: mechanically flattening the titanium substrate treated in step 2 at high temperature;

[0010] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution to etch the sharp parts of the titanium substrate surface smooth and remove the oxide scale on the surface;

[0011] Step 5, cleaning and drying: cleaning the titanium substrate treated in step 4 to remove the dirt remaining on the surface of the titanium substrate, and drying;

[0012] Step 6: preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti=1:9-9:1, wherein Pd:Pt=1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0013] Step 7: preparing an active layer coating solution: fully dissolving ruthenium trichloride in an n-butanol solution to form a solution E; fully dissolving butyl titanate in an n-butanol solution to form a solution F; fully dissolving chloropalladic acid in an n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium to palladium to titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0014] Step 8: coating and hot pressing sintering: the bottom coating solution is applied to the surface of the titanium substrate treated in step 5, and the solvent is evaporated; the titanium substrate is then hot pressed; after hot pressing, the titanium substrate is naturally cooled at room temperature, and the bottom solution is applied for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is not less than 0.1 mg / cm 2 Then the active layer coating liquid is applied and hot pressed and sintered. The active layer coating liquid treatment method is the same as the bottom coating liquid treatment method until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; Anode preparation is completed.

[0015] Preferably, the sand used for the sandblasting in step 2 is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:2-1:9.

[0016] Preferably, the heat leveling treatment in step 3 adopts a heavy object flattening operation, and the weight is 3-5t.

[0017] Preferably, the acid treatment in step 4 is carried out for 1.5 to 3 hours.

[0018] Preferably, the hot pressing in step 8 is for 15 min, the pressure is 1-5t, and the temperature is 450° C.; when the last hot pressing sintering is performed, the titanium substrate active layer is hot pressed at 450° C. for 1 h.

[0019] The technical solution adopted by the present invention is a method for testing the durability of an anode for an electrolytic water sterilizer. The prepared anode is used as a positive electrode and placed in an electrolytic cell. The electrolysis is stopped every 5-10 minutes, and the electrolysis is continued for the next 5-10 minutes. The electrolysis is repeated until the anode fails. The power supply is set to a constant voltage mode, and the voltage can be 12-24V. The start time and the anode failure time are calculated, which is the anode test life.

[0020] Preferably, the electrolyte solution is configured with an extreme water quality of 450 mg / L total hardness in accordance with GB / T23119-2017.

[0021] Preferably, the negative electrode is a titanium substrate.

[0022] The technical solution adopted by the present invention is an anode durability testing device for an electrolytic water sterilizer, comprising: a liquid storage tank, a conveying device, a power supply, a relay, and an electrolytic cell, wherein the power supply is connected to the relay; the relay is connected to the electrolytic cell through a wire; a prepared anode sheet is arranged inside the electrolytic cell as a positive electrode, and a titanium substrate is a negative electrode; an overflow port is arranged above one side wall of the electrolytic cell, and the overflow port is connected to the liquid storage tank through a pipeline; one end of the conveying device is connected to the liquid storage tank through a pipeline, and the other end is connected to the electrolytic cell through a pipeline.

[0023] Preferably, the prepared anode sheet is directly opposite to the titanium substrate, and the inter-electrode distance is 1-3 mm.

[0024] Preferably, the conveying device is a peristaltic pump, and the peristaltic pump is set to have a water inlet flow rate of 25-50 ml / min.

[0025] The present invention uses a hot pressing sintering method, which can greatly improve the bonding strength between the anode coating and the titanium substrate; the present invention uses a hot pressing sintering method, which can solve the unevenness of the anode caused by the high-temperature sintering preparation process, and reduce the probability of the anode causing a short circuit during the electrolysis process due to the unevenness of the anode; the present invention selects a mixture of palladium and platinum with strong oxidation resistance as the bottom layer, and the addition of palladium and platinum in the bottom layer is beneficial to improving the oxidation resistance of the coating, greatly improving the service life of the anode. The present invention uses the use of the anode sheet in actual working conditions as a standard, and accumulates countless electrolysis times to calculate the anode life. This test method can very realistically and reliably reflect the actual use time of the anode. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the testing device of the present invention.

[0027] In the figure: 1, power supply; 2, relay; 3, electrolytic cell; 4, peristaltic pump; 5, liquid storage tank; 6, wire. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention clearer and more understandable, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings.

[0029] The present invention is a method for preparing an anode for an electrolytic water sterilizer. The preparation of the anode for an electrolytic water sterilizer is divided into the following steps:

[0030] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0031] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:2-1:9;

[0032] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight of the weight is 3-5 t;

[0033] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 1.5-3 hours to etch the sharp parts of the titanium substrate surface smooth and remove the oxide scale on the surface;

[0034] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove dirt remaining on the surface of the titanium substrate, and drying;

[0035] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti=1:9-9:1, wherein Pd:Pt=1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0036] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0037] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 1-5t, and the temperature is 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is not less than 0.1mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0038] The following are specific embodiments:

[0039] Embodiment 1:

[0040] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0041] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1 to further increase its surface area; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:2;

[0042] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight is 3 tons;

[0043] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 1.5 hours, etching the sharp parts of the surface of the titanium substrate after mechanical treatment smooth, and removing the oxide scale on the surface;

[0044] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove the dirt remaining on the surface of the titanium substrate treated in step 4, and drying;

[0045] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti = 1:9, wherein Pd:Pt = 1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0046] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0047] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 3t, and the temperature can be 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is 0.5mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0048] Embodiment 2:

[0049] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0050] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1 to further increase its surface area; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:4;

[0051] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight is 3 tons;

[0052] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 2 hours, etching the sharp parts of the surface of the titanium substrate after mechanical treatment smooth, and removing the oxide scale on the surface;

[0053] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove the dirt remaining on the surface of the titanium substrate treated in step 4, and drying;

[0054] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium to platinum to titanium is: Pd+Pt:Ti = 9:1, wherein Pd:Pt = 1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0055] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0056] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 3t, and the temperature can be 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is 0.5mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0057] Embodiment 3:

[0058] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0059] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1 to further increase its surface area; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:3;

[0060] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight is 3 tons;

[0061] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 3 hours, etching the sharp parts of the surface of the titanium substrate after mechanical treatment smooth, and removing the oxide scale on the surface;

[0062] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove the dirt remaining on the surface of the titanium substrate treated in step 4, and drying;

[0063] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti = 4:1, wherein Pd:Pt = 1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0064] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0065] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 3t, and the temperature can be 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is 0.5mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0066] Embodiment 4:

[0067] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0068] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1 to further increase its surface area; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:5;

[0069] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight is 3 tons;

[0070] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 3 hours, etching the sharp parts of the surface of the titanium substrate after mechanical treatment smooth, and removing the oxide scale on the surface;

[0071] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove the dirt remaining on the surface of the titanium substrate treated in step 4, and drying;

[0072] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti = 4:1, wherein Pd:Pt = 1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0073] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0074] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 3t, and the temperature can be 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is 0.8mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0075] Embodiment 5:

[0076] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0077] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1 to further increase its surface area; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:6;

[0078] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight is 3 tons;

[0079] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 1.5 hours, etching the sharp parts of the surface of the titanium substrate after mechanical treatment smooth, and removing the oxide scale on the surface;

[0080] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove the dirt remaining on the surface of the titanium substrate treated in step 4, and drying;

[0081] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti = 4:1, wherein Pd:Pt = 1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0082] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0083] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 3t, and the temperature can be 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is 1.2mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0084] Embodiment 6:

[0085] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0086] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1 to further increase its surface area; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:8;

[0087] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight is 3 tons;

[0088] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 2 hours, etching the sharp parts of the surface of the titanium substrate after mechanical treatment smooth, and removing the oxide scale on the surface;

[0089] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove the dirt remaining on the surface of the titanium substrate treated in step 4, and drying;

[0090] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti = 4:1, wherein Pd:Pt = 1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0091] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0092] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 1t, and the temperature can be 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is 0.5mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0093] Embodiment 7:

[0094] Step 1, cutting and forming: Cut the prepared TA1 titanium substrate into 5 square pieces of 100mm*100mm*1mm;

[0095] Step 2, sandblasting: sandblasting the titanium substrate treated in step 1 to further increase its surface area; the sand is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:9;

[0096] Step 3, thermal leveling: applying a weight to the titanium substrate treated in step 2 at high temperature to perform a mechanical flattening operation, wherein the weight is 3 tons;

[0097] Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution for 3 hours, etching the sharp parts of the surface of the titanium substrate after mechanical treatment smooth, and removing the oxide scale on the surface;

[0098] Step 5, cleaning and drying: placing the titanium substrate treated in step 4 in a high-power ultrasonic machine for ultrasonic cleaning to remove the dirt remaining on the surface of the titanium substrate treated in step 4, and drying;

[0099] Step 6, preparing a primer coating liquid: fully dissolving chloroplatinic acid in a n-butanol solution to form a solution A; fully dissolving chloropalladic acid in a n-butanol solution to form a solution B; fully dissolving butyl titanate in a n-butanol solution to form a solution C; mixing solutions A, B and C, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the primer coating liquid; in the primer coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti = 4:1, wherein Pd:Pt = 1:3, and the concentration of the primer coating liquid is 0.5 mol / L;

[0100] Step 7, preparing an active layer coating solution: fully dissolving ruthenium trichloride in a n-butanol solution to form a solution E; fully dissolving butyl titanate in a n-butanol solution to form a solution F; fully dissolving chloropalladic acid in a n-butanol solution to form a solution G; mixing solutions E, F and G, and adding hydrochloric acid, wherein the hydrochloric acid content is 5% of the volume of the mixed solution, to form the active layer coating solution; in the active layer coating solution, the mass ratio of ruthenium palladium titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L;

[0101] Step 8, coating and hot pressing sintering: brush the bottom solution on the surface of the titanium substrate treated in step 5, place it on a heating plate at 60°C, and evaporate the solvent; place the titanium material with the evaporated solvent on a hot press at 450°C, and perform hot pressing for 15 minutes, the pressure can be 5t, and the temperature can be 450°C; after hot pressing, the titanium substrate is naturally cooled to below 30°C at room temperature, and the bottom layer is brushed for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is 0.5mg / cm 2 ; Apply the active layer, the active layer solution is applied and hot pressed in the same way as the bottom solution, until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; and during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour; the anode preparation is completed.

[0102] The present invention is a method for testing the durability of an anode for an electrolytic water sterilization and disinfection device. The method for testing the durability is as follows:

[0103] The electrolyte solution is configured in accordance with GB / T23119-2017 with an extreme water quality of 450 mg / L total hardness.

[0104] The anode sheet prepared by the anode preparation method for the electrolytic water sterilizer is placed in the electrolytic cell 3, and a titanium substrate is set as the negative electrode. The electrolysis is stopped every 5-10 minutes, and the electrolysis is continued for the next 5-10 minutes. The electrolysis is repeated until the anode fails; the power supply is set to a constant voltage mode, and the voltage can be 12-24V; the start time and the anode failure time are calculated, which is the anode test life.

[0105] By calculating the start time and the anode failure time, the anode test life can be calculated.

[0106] The present invention is a device for testing the durability of an anode used in an electrolytic water sterilization and disinfection device. The device for testing the durability is:

[0107] like Figure 1As shown, the durability performance testing device includes a liquid storage tank 5, a conveying device, a power supply 1, a relay 2, and an electrolytic cell 3.

[0108] The power supply 1 is a DC regulated power supply, and the power supply 1 is connected to the relay 2 , and the power supply 1 is used to provide a current with appropriate power.

[0109] The relay 2 is connected to the electrolytic cell via a wire 6, and the relay 2 is used to control the electrolysis state.

[0110] An anode prepared by a method for preparing an anode for electrolytic water sterilization and disinfection device is arranged inside the electrolytic cell 3 as a positive electrode, a titanium substrate is arranged as a negative electrode, two electrodes are directly opposite to each other, and the inter-electrode distance is controlled to be 1-3 mm, and a conductive column is arranged on the electrode, and the conductive column and the wire 6 are sealed by corrosion-resistant glue to prevent corrosion; the electrolytic cell 3 is open, and an overflow port is arranged above one side wall of the electrolytic cell 3, and the overflow port is connected to the liquid storage tank 5 through a pipeline;

[0111] The liquid storage tank 5 is provided with a tank cover, and a small hole is provided at one end of the top of the tank cover, and the small hole is connected to the pipeline;

[0112] The conveying device is a peristaltic pump 4, one end of the peristaltic pump 4 is connected to the liquid storage tank 5 through a pipeline, and the other end is connected to the electrolytic cell 3 through a pipeline. The peristaltic pump 4 can control the water inlet flow rate, and the water inlet flow rate is set to 25-50ml / min.

[0113] The titanium electrode obtained in the above embodiment and the ruthenium-iridium-titanium electrode purchased from the market were subjected to life tests using the life test device and method set by the invention. The results are shown in Table 1, as shown below:

[0114]

[0115] The relay is set to stop electrolysis every 5 minutes and continue electrolysis for the next 5 minutes; the voltage of the power supply 1 described in Example 1 is set to 12V, and the voltage of the power supply 1 described in Examples 2 to 7 is set to 24V; the volume of the liquid storage tank 5 is 200L; the volume of the electrolytic cell 3 is 1L; the water inlet flow rate of the peristaltic pump 4 is set to 25ml / min; the inter-electrode distance between the two anodes in Example 1 is 1mm; the inter-electrode distance between the two anodes in Examples 2 to 7 is 3mm.

[0116] Table 2 shows the percentage increase in lifespan when comparing each embodiment of the present invention with the comparative example, as shown in the following table:

[0117]

[0118] It can be seen that the anode prepared by the present invention has a longer lifespan than the anode prepared by the prior art.

[0119] The titanium electrodes obtained in the above embodiments and the ruthenium-iridium-titanium electrodes purchased from the market were tested for flatness using a marble platform and a feeler gauge. The results are shown in Table 3, as shown below:

[0120]

[0121] It can be seen from Table 3 that the flatness of the anode sheets prepared in the above embodiments is lower than that of the anode sheets prepared in the prior art.

[0122] In summary, the present invention improves the oxidation resistance of the electrode by introducing palladium and platinum with strong oxidation resistance into the bottom layer; through hot pressing sintering, the bonding strength between the electrode coating and the substrate and the flatness of the electrode are improved. It is highly innovative and practical and can better meet market demand.

Claims

1. A method for preparing an anode for an electrolytic water sterilizer, characterized in that: The following steps are involved: Step 1, cutting and forming: cutting and forming the titanium substrate; Step 2, sandblasting: performing surface sandblasting on the titanium substrate treated in step 1; Step 3, thermal leveling: mechanically flattening the titanium substrate treated in step 2 at high temperature; Step 4, acid treatment: etching the titanium substrate treated in step 3 in a boiling oxalic acid solution to etch the sharp parts of the titanium substrate surface smooth and remove the oxide scale on the surface; Step 5, cleaning and drying: cleaning the titanium substrate treated in step 4 to remove the dirt remaining on the surface of the titanium substrate, and drying; Step 6: Prepare the bottom coating solution: fully dissolve chloroplatinic acid in n-butanol solution to form solution A; Fully dissolving chloropalladic acid in n-butanol solution to form solution B; Fully dissolving butyl titanate in n-butanol solution to form solution C; Mixing solution A, solution B and solution C, and adding hydrochloric acid, wherein the content of hydrochloric acid is 5% of the volume of the mixed solution, to form the bottom coating solution; In the bottom coating liquid, the mass ratio of palladium, platinum and titanium is: Pd+Pt:Ti=1:9–9:1, wherein Pd:Pt=1:3, and the concentration of the bottom coating liquid is 0.5 mol / L; Step 7: preparing an active layer coating solution: fully dissolving ruthenium trichloride in n-butanol solution to form solution E; Fully dissolving butyl titanate in n-butanol solution to form solution F; Fully dissolving chloropalladic acid in n-butanol solution to form solution G; Mixing solution E, solution F and solution G, and adding hydrochloric acid, wherein the content of hydrochloric acid is 5% of the volume of the mixed solution, to form the active layer coating solution; In the active layer coating solution, the mass ratio of ruthenium to palladium to titanium is: Ru:Pd:Ti=2:1:6, and the concentration of the active layer coating solution is 0.5 mol / L; Step 8: coating and hot pressing sintering: the bottom coating solution is applied to the surface of the titanium substrate treated in step 5, and the solvent is evaporated; the titanium substrate is then hot pressed; after hot pressing, the titanium substrate is naturally cooled at room temperature, and the bottom solution is applied for the second time, and the above coating and hot pressing sintering methods are repeated until the mass of Pd in ​​the titanium substrate is not less than 0.1 mg / cm 2 Then the active layer coating liquid is applied and hot pressed and sintered. The active layer coating liquid treatment method is the same as the bottom coating liquid treatment method until the ruthenium content in the active layer solution is 0.6 mg / cm 2 , palladium content is 0.3mg / cm 2 ; Anode preparation is completed.

2. According to the method for preparing an anode for an electrolytic water sterilizer according to claim 1, the sand used for the sandblasting in step 2 is white corundum, and the particle sizes are 16# and 24#, respectively, and the ratio of 16# sand to 24# sand is 1:2-1:

9.

3. According to the method for preparing an anode for an electrolytic water sterilizer according to claim 1, the heat leveling treatment in step 3 adopts a heavy object flattening operation, and the weight is 3-5t.

4. The method for preparing an anode for an electrolytic water sterilizer according to claim 1, wherein the acid treatment in step 4 is carried out for 1.5 to 3 hours.

5. According to the method for preparing an anode for an electrolytic water sterilizer according to claim 1, the hot pressing in step 8 is 15 minutes, the pressure is 1-5t, and the temperature is 450°C; during the last hot pressing sintering, the titanium substrate active layer is hot pressed at 450°C for 1 hour.

6. A method for testing the durability of anodes for electrolytic water sterilization and disinfection, characterized in that: The anode prepared according to any one of claims 1 to 5 is used as a positive electrode and placed in an electrolytic cell, the electrolysis is stopped every 5-10 minutes, and the electrolysis is continued for the next 5-10 minutes, and the electrolysis is repeated until the anode fails; the power supply is set to a constant voltage mode, and the voltage can be 12-24V; The anode test life is calculated by calculating the starting time and the anode failure time.

7. The method for testing the durability of anodes for electrolytic water sterilization and disinfection according to claim 6, characterized in that: The electrolyte solution is configured with an extreme water quality of 450 mg / L total hardness.

8. The method for testing the durability of anodes for electrolytic water sterilization and disinfection according to claim 6, characterized in that: The negative electrode is a titanium substrate.

9. An anode durability testing device for electrolytic water sterilization and disinfection device, characterized in that: include: A liquid storage tank, a conveying device, a power supply, a relay, and an electrolytic cell, wherein the power supply is connected to the relay; the relay is connected to the electrolytic cell through a wire; the electrolytic cell is provided with an anode sheet prepared according to any one of claims 1 to 5 as a positive electrode, and a titanium substrate is a negative electrode; an overflow port is provided above one side wall of the electrolytic cell, and the overflow port is connected to the liquid storage tank through a pipeline; one end of the conveying device is connected to the liquid storage tank through a pipeline, and the other end is connected to the electrolytic cell through a pipeline.

10. The anode durability testing device for electrolytic water sterilization and disinfection device according to claim 9, characterized in that: The anode sheet is directly opposite to the titanium substrate, and the inter-electrode distance is 1-3 mm.

11. The anode durability testing device for electrolytic water sterilization and disinfection device according to claim 9, characterized in that: The conveying device is a peristaltic pump, and the peristaltic pump is set with a water inlet flow rate of 25-50 ml / min.

Citation Information

Patent Citations

  • Fabrication method of long-life titanium base electrode

    CN103014755B

  • Conductive coating for metal electrode - consisting of mixed oxides of at least three metals

    BE785605A

  • AU8932798A